Neologizmy w korespondencji prywatnej Henryka Sienkiewicza - Mariak, Leonarda (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The aim of this article is to examine the structure and the functions of neologisms included in the private letters of Henryk Sienkiewicz. The analysis of the lexis presented in this paper reveals that the writer tended to use the word-formative neologisms, semantical neologisms and functional neologisms most frequently. The expressive function of this neologisms is the prevailing one.